O juiz das garantias no ordenamento jurídico brasileiro: (in)constitucionalidade, (in)convencionalidade e (des)aperfeiçoamento - Santana, Henrique Cavalcanti de (2021)
The institute of the Guarantee Judge, inserted in the legal system by Law 13.964/2019, which informs the improvement of the Brazilian criminal process, was subject of constitutional review and its effectiveness has been suspended as a precautionary measure until the full consideration of the STF. In this context, the main objective of this research is to study the constitutionality and conventionality of the institute, as well as whether it improves our procedural system. The insertion of the Guarantee Judge is considered the greatest change in the Brazilian criminal procedure in more than 80 years and redesigns the dynamics of criminal prosecution, with the promise to improve the impartiality of the judge. The research theoretical thread is the Constitutional and Democratic State of Law, with contributions from the study of comparative law and from theories of social psychology. This research is descriptive and exploratory with a qualitative approach, hypothetical-deductive method through bibliographic and documental procedure. In conclusion, it will be presented that the institute improves the system, but presents provisions of dubious constitutionality. It is understood that there is a fertile field to be developed in the academy, mainly for verifying what were the associations representing the magistracy state and federal the first ones to argue about the unconstitutionality of the Guarantee Judge. This fact portrays, in the last instance, the octogenarian struggle against an inquisitorial criminal process, born from Mussolini's Italian criminal process, of fascist matrix, which the search for real truth legitimated the judicial leadership, nowadays, the judge punisher.